Management of salivary gland malignant tumor: the Policlinico Umberto I, "Sapienza" University of Rome Head and Neck Unit clinical recommendations. (December 2017) - De Felice, Francesca; de Vincentiis, Marco; Valentini, Valentino; Musio, Daniela; Mezi, Silvia; Lo Mele, Luigi; Della Monaca, Marco; D'Aguanno, Vittorio; Terenzi, Valentina; Di Brino, Martina; Brauner, Edoardo; Bulzonetti, Nadia; et al.
Highlights: Salivary gland malignant tumor (SGMT) represents a rare entity. Multidisciplinary approach, as well as management in a specialist centre are paramount. This analysis provides reasonable clinical recommendations based on primary tumor location. Abstract: Salivary gland malignant tumor (SGMT) is a malignant disease requiring multidisciplinary approach. The rare incidence and the consequent lack of robust evidence-based medicine has called for a comprehensive update to draw recommendations for clinical practice. This paper is a summary of the XXX Head and Neck Unit guidelines regarding the management of SGMT. Recommendations include the indications for exclusive and adjuvant therapy, as well as metastatic management, for both major and minor SGMT.